Hodgkin's disease and renal paraneoplastic syndromes in childhood - Büyükpamukçu, Münevver; Hazar, Volkan; Tınaztepe, Keriman; Bakkaloğlu, Ayşın; Akyüz, Canan; Kutluk, Tezer (The Turkish Journal of Pediatrics, 2000)
The purpose of this study was to investigate children followed as having both Hodgkin's disease (HD) and nephropathy and discuss the factors which might play roles in the pathogenesis of this association by reviewing the pertinent literature. Our experience among 661 children with HD revealed ten cases (1.5%) with nephropathy; eight of these were biopsy proven. Tissue diagnoses were amyloidosis (AA type) in four cases, and membranoproliferative glomerulonephritis and minimal change glomerulopathy in two cases each. Sex distribution was equal. There was a predominance of the mixed cellular (MC) histologic type in our patients with HD. Nephropathy was shown to antedate the diagnosis of HD in two cases and to herald a relapse in one. In brief, the development of a nephropathy in a patient with HD can be considered as a paraneoplastic phenomenon. Renal amyloidosis may already be present at the time of diagnosis of HD and must be kept in mind as a cause of proteinuria due to preexisting nephropathy. Developing renal paraneoplastic syndrome, even in early-staged HD, in children, may be a poor prognostic factor.
Keywords: nephropathy; paraneoplastic phenomenon; childhood; Hodgkin's disease